Report of the Committee Set up to Study the Scope and Possibilities of Intensifying Compost Programme in the Country - Planning Commission (Planning Commission, Government of India, 1968)
The Report on Intensifying the Compost Programme in India, led by Shri K.A.P. Stevenson in 1966, evaluates strategies to enhance composting and organic waste management nationwide, with a particular focus on large urban centers and agricultural sustainability. The committee identified mechanical composting as a practical solution for cities, providing sanitary control, consistent year-round operation, rapid production of high-quality compost, and recovery of recyclable materials, though it could process only about 50% of urban waste. Recognizing the significant consumption of cow dung as fuel, the report recommends alternative energy sources such as fuelwood plantations on rural waste lands, promotion of cow dung gas plants, and increased use of soft coke, supported by public awareness campaigns and logistical improvements. Additionally, the report emphasizes optimizing agricultural, forestry, and industrial waste for manure production, suggesting nationwide surveys and pilot projects to test feasibility and efficiency. Recommendations include establishing pilot mechanical composting plants, fostering community participation, and integrating multi-agency collaboration to implement these innovations effectively. Overall, the report underscores the critical need for systematic composting programs and alternative energy strategies to enhance soil fertility, promote sustainable agriculture, and address environmental concerns in India, marking a significant step toward holistic rural and urban waste management solutions.
Planning Commission, Government of India
Keywords: Compost Programme; Mechanical Composting; Urban Waste Management; Cow Dung Conservation; Fuelwood Plantations; Soft Coke; Agricultural Waste Utilization; Organic Manure; Rural Energy Solutions; Pilot Projects; Soil Fertility; Sustainable Agriculture